2008
DOI: 10.2140/gt.2008.12.351
|View full text |Cite
|
Sign up to set email alerts
|

Projective structures, grafting and measured laminations

Abstract: We show that grafting any fixed hyperbolic surface defines a homeomorphism from the space of measured laminations to Teichmüller space, complementing a result of Scannell-Wolf on grafting by a fixed lamination. This result is used to study the relationship between the complex-analytic and geometric coordinate systems for the space of complex projective (CP 1 ) structures on a surface.We also study the rays in Teichmüller space associated to the grafting coordinates, obtaining estimates for extremal and hyperbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…The map λ → gr −1 λ (Y ) is injective (see [11]), establishing a bijection between W Y ∩ T(S) and ML Z (S). In particular, the set W Y ∩ T(S) is infinite, which is used in [10] to show that W Y is not an algebraic variety.…”
Section: Graftingmentioning
confidence: 96%
“…The map λ → gr −1 λ (Y ) is injective (see [11]), establishing a bijection between W Y ∩ T(S) and ML Z (S). In particular, the set W Y ∩ T(S) is infinite, which is used in [10] to show that W Y is not an algebraic variety.…”
Section: Graftingmentioning
confidence: 96%
“…Grafting construction This is more widespread in the literature (see e.g. [16] or [9] for an account). The idea is to cut S open along γ and insert a Euclidean cylinder [0, l] × γ , l ≥ 0 with the appropriate twist parameter (details below (1.4)).…”
Section: Fenchel-nielsen Constructionmentioning
confidence: 99%
“…Building on the Scannell-Wolf result, the author and Wolf showed that the X-grafting map is also a local homeomorphism, leading to: Theorem 4.4 (Dumas and Wolf [27]). For each X ∈ T (S), the X-grafting map gr X : ML(S) → T (S) is a homeomorphism.…”
Section: Conformal Grafting Mapsmentioning
confidence: 99%